Functional genomics identified a novel protein tyrosine phosphatase receptor type f‐mediated growth inhibition in hepatocarcinogenesis. Issue 6 (25th April 2014) - Bera, Rabindranath; Chiou, Chih‐Yung; Yu, Ming‐Chin; Peng, Jei‐Ming; He, Chung‐Ru; Hsu, Chih‐Yun; Huang, Hsiao‐Ling; Ho, Uda Y.; Lin, Shi‐Ming; Lin, Yu‐Jr; Hsieh, Sen‐Yung
<x xml:space="preserve">Abstract</x> It is unclear how proliferating cells elicit suppression on cell proliferation and how cancer cells evade this growth suppression. Using a loss‐of‐function screening of the human kinome and phosphatome to identify genes suppressing tumor initiation in human hepatocellular carcinoma (HCC), we identified 19 genes and characterized one of the top‐scoring tumor suppressor candidates, protein tyrosine phosphatase receptor type F (PTPRF). We found that PTPRF was induced during cell proliferation by cell‐cell contact. Ectopic expression of wild‐type PTPRF, but not the phosphatase‐inactive mutant, suppressed cell proliferation and colony formation in soft‐agar assays. In contrast, PTPRF silencing led to cell hyperproliferation, enhanced tumor colony formation in soft agar, and increased xenograft tumor growth in nude mice. Mechanistically, PTPRF silencing showed aberrant ERK‐dependent signaling including the phosphorylation/stabilization of v‐myc avian myelocytomatosis viral oncogene homolog (MYC) through the direct activation of v‐src avian sarcoma viral oncogene homolog (SRC) and suppression of PP2A. This PTPRF‐mediated growth suppression during cell proliferation functioned independently of the Hippo‐Yap pathway. Clinically, PTPRF was down‐regulated in 42% HCC (37/89), 67% gastric cancer (27/40), and 100% colorectal cancer (40/40). PTPRF up‐regulation was found in 24% HCC (21/89) and associated with better clinical outcomes. Conclusion: A novel PTPRF‐mediated growth suppression pathway was identified by way of a functional genomics screening in human hepatoma cells. Induction of PTPRF by cell‐cell contact during cell proliferation quenched the activated ERK‐dependent proliferation signaling to prevent cell hyperproliferation and tumor initiation. PTPRF down‐regulation in HCC facilitated tumor development. Our findings shed light on how cancer cells can evade growth suppression and open a new avenue for future development of anticancer therapies. (Hepatology 2014;59:2238–2250)